2014
DOI: 10.1080/19345747.2013.836763
|View full text |Cite
|
Sign up to set email alerts
|

Helping ELLs Meet the Common Core State Standards for Literacy in Science: The Impact of an Instructional Intervention Focused on Academic Language

Abstract: The goal of this study was to assess the effectiveness of an intervention-Quality English and Science Teaching 2-designed to help English language learners (ELLs) and their English proficient classmates develop academic language in science, as required by the Common Core State Standards. The intervention consisted of supplementary instructional materials and professional development. Participants included 1,309 students, of whom 353 were ELLs. Sixty sections taught by 15 teachers in seven middle schools were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 25 publications
2
34
0
Order By: Relevance
“…A possibly even more troubling finding was reported in a meta‐analysis of inquiry science education for ELs and non‐ELs, in which August et al’s (2009, 2014) studies were included. Estrella et al (2018) found that inquiry science instruction for ELs was modestly more effective in promoting learning of science knowledge and literacy as compared with traditional or business‐as‐usual instruction (mean effect size = 0.28).…”
Section: Beyond Foundational Skills and Beginning And Early Readingmentioning
confidence: 99%
“…A possibly even more troubling finding was reported in a meta‐analysis of inquiry science education for ELs and non‐ELs, in which August et al’s (2009, 2014) studies were included. Estrella et al (2018) found that inquiry science instruction for ELs was modestly more effective in promoting learning of science knowledge and literacy as compared with traditional or business‐as‐usual instruction (mean effect size = 0.28).…”
Section: Beyond Foundational Skills and Beginning And Early Readingmentioning
confidence: 99%
“…The remaining studies were classed as medium (Hwang et al, 2015) and low (Lesaux et al, 2014). The intervention effects seen ranged from small (August et al, 2014;Lesaux et al, 2014) to large (Crosson & Moore, 2017). Effect sizes were not reported by Hwang et al (2015).…”
Section: Tablementioning
confidence: 99%
“…Despite this, the research is scant specifically regarding EL and EC students and the exploration of the relationship between academic language and overarching conceptual understanding in science. However, a few researchers (e.g., [12,13,[26][27][28][29][30]) have provided solid evidence that inquiry-based instructions increase, in particular, ELs' and ECs' conceptual understanding of science, particularly when literacy is connected to science instruction. The inquiry-based instruction referred to in our study includes engaging ELs and ECs in practices such as asking questions, planning investigations, developing models, and interpreting data, all while promoting language and literacy skills.…”
Section: Literacy-infused Inquiry-based Science For Els and Ecsmentioning
confidence: 99%